(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Neonatal Sepsis is a bacterial infection of the blood in a neonate and an infant younger than 4 weeks of age. The analytical profile index or API is a classification of bacteria based on experiments, allowing fast identification. This system is developed for quick identification of clinically relevant bacteria. Objective: To identify the pattern of organisms in neonatal sepsis using API system in Baghdad City hospital, Al-Imamein Al-Kadhimein Medical City and Central Pediatrics Teaching Hospital. Methods: In this cross-sectional study, blood samples from 100 neonatal patients were inoculated into a blood culture bottle and incubated at 37 °C under aerobic conditions, subculture was done after 24 h of incubation, the growth was identified by phenotypic characteristics, gram’s stain, and API system. Results: Positive blood cultures were detected in 82 (82%), according to API system the most prominent bacterial isolates from blood culture in neonates with early-onset sepsis were non-coagulase Staphylococcus (20.4%) Staphylococcus aureus (18.1 %), Acinetobacter bumanii (13.6%), Pseudomonas aeruginosa (11.36 %), Streptococcus agalactiae (11.3 %), while in late-onset sepsis the most common bacteria were Staphylococcus aureus (21.0%), non-coagulase Staphylococcus (13.1%), Citrobacter freundii and Pseudomonas aeruginosa (10.5 %) respectively. Conclusion: The API 20E may be useful for the identification of the bacterial species rarely described as pathogens in neonatal sepsis will help us to study the clinical burden resulting from the emergence of these species as causes for this neonatal infection. Keywords: Early-onset sepsis, late-onset sepsis, blood culture, API system Citation: Al-Mossawi HSM, Hassan JS, Al-bashier NM, Al-Omrani AAA. Identification common cause of neonatal sepsis by analytical profile index system (API). Iraqi JMS. 2018; 16(3): 327-334. doi: 10.22578/IJMS.16.3.12